1985
DOI: 10.1021/bi00341a051
|View full text |Cite
|
Sign up to set email alerts
|

Differential processing and regulation of thyroid-stimulating hormone subunit carbohydrate chains in thyrotropic tumors and in normal and hypothyroid pituitaries

Abstract: Thyroid-stimulating hormone (TSH) alpha- and beta-subunit glycosylation was investigated in mouse thyrotropic tumor and in normal and hypothyroid pituitary cells for various periods of time in the presence of [3H]mannose or [3H]galactose. After sequential precipitation with anti-alpha and anti-beta sera, subunits were treated with Pronase followed by endo-beta-N-acetylglucosaminidase H (Endo H) and analyzed by paper chromatography. In primary cultures of thyrotropic tumor cells incubated for 60 min with [3H]ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1986
1986
1997
1997

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 38 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…These species are generally similar to lipid-linked oligosaccharides extracted from hepatocytes and other cell types (62,63). After short 10-min incubations of thyrotropes with [ 3 H] mannose, Glc 3 Man 9 GlcNAc 2 oligosaccharides were detected bound to some cellular glycoproteins, but this very early glucose-containing precursor was not found linked to nascent TSH subunits (65)(66)(67), suggesting either that TSH subunits were initially glycosylated with a nonglycosylated precursor, or that the glucose residues were very rapidly trimmed from the TSH subunits. When Stannard et al (68) employed the glucosidase inhibitor 1-deoxynojirimycin in 1988 it became clear that very rapid glucose trimming was the more likely explanation.…”
Section: High-mannose Oligosaccharides Of Tsh Subunit Precursorsmentioning
confidence: 77%
See 2 more Smart Citations
“…These species are generally similar to lipid-linked oligosaccharides extracted from hepatocytes and other cell types (62,63). After short 10-min incubations of thyrotropes with [ 3 H] mannose, Glc 3 Man 9 GlcNAc 2 oligosaccharides were detected bound to some cellular glycoproteins, but this very early glucose-containing precursor was not found linked to nascent TSH subunits (65)(66)(67), suggesting either that TSH subunits were initially glycosylated with a nonglycosylated precursor, or that the glucose residues were very rapidly trimmed from the TSH subunits. When Stannard et al (68) employed the glucosidase inhibitor 1-deoxynojirimycin in 1988 it became clear that very rapid glucose trimming was the more likely explanation.…”
Section: High-mannose Oligosaccharides Of Tsh Subunit Precursorsmentioning
confidence: 77%
“…When Stannard et al (68) employed the glucosidase inhibitor 1-deoxynojirimycin in 1988 it became clear that very rapid glucose trimming was the more likely explanation. In the earlier studies (65)(66)(67) it was also apparent that there was differential processing of the high-mannose units of TSH as compared to free a-subunits, which also differed from that of the bulk of glycoproteins in these cells. The rate of trimming of a mannose residue from Man 9 GlcNAc 2 to produce Man 8 GlcNAc 2 units appeared to be much faster for free a-subunits; after a 60-min incubation with [ 3 H]mannose, Man 8 GlcNAc 2 units predominated in free a-subunits, whereas Man 9 GlcNAc 2 units still predominated in TSH heterodimers and in other cellular glycoproteins.…”
Section: High-mannose Oligosaccharides Of Tsh Subunit Precursorsmentioning
confidence: 96%
See 1 more Smart Citation
“…We have also demonstrated that chemical deglycosylation of TSH greatly reduces its bioactivity and produces a form that acts as a competitive antagonist (36). Since thyroid hormones have been shown to affect TSH glycosylation in rodents (37,38), our present study suggests that they may also affect posttranslational TSH carbohydrate processing in man, either by a direct effect on the thyrotrophs or indirectly through TRH release and secretion.…”
Section: Discussionmentioning
confidence: 50%